Investigating Structural Relationship among Service Quality Dimensions, Customer Satisfaction, and Customer Loyalty for Conventional Bank Customers: Evidence from Bangladesh - Miah, Md. Shelim (Asian Business Review, 2021)
Customers of the banks are highly servicing sensitive in Bangladesh. The quality of service has become an integral part of customer satisfaction. Day by day, It has been demonstrated that customer satisfaction and loyalty are linked to service quality. There is also a link between service quality and customer satisfaction, and customer loyalty in banks. Therefore, this paper investigated the effect of service quality factors on customer satisfaction and the relationship between customer satisfaction and customer loyalty in conventional banks in Bangladesh. A survey was conducted on 13 different conventional banks in Bangladesh. Using simple random sampling, 220 customers were selected as a sample from selected conventional banks for this study. The research was carried out using a structured questionnaire. The SPSS software was used to analyze the demographic data. Multivariate analysis technique like Factor Analysis and Structural Equation Modeling (SEM) was used to identify the influential factors for the bank's customer loyalty by using SmartPLS3 software. The study found that all service quality factors such as assurance, reliability, responsiveness, and tangibility are the influential factors except empathy.
Keywords: Service Quality; Structural Equation Modeling; Customer Satisfaction; Customer Loyalty; Conventional Banks; Bangladesh